Late Complications of COVID-19; An Umbrella Review on Current Systematic Reviews - SeyedAhmad SeyedAlinaghi; AmirBehzad Bagheri; Armin Razi; Paniz Mojdeganlou; Hengameh Mojdeganlou; Amir Masoud Afsahi; Arian Afzalian; Parinaz Paranjkhoo; Ramin Shahidi; Pegah Mirzapour; Zahra Pashaei; Mohammad Amin Habibi; et al. (Archives of Academic Emergency Medicine, 2023)
Introduction: Several clinical manifestations have been discovered for COVID-19 since the emergence of SARS-CoV-2, which can be classified into early, medium, and long-term complications. However, late complications can be present after recovery from acute COVID-19 illness. The present study aims to comprehensively review the available evidence of late complications related to COVID-19.